2016
DOI: 10.17811/ebl.5.4.2016.113-124
|View full text |Cite
|
Sign up to set email alerts
|

Political instability and stock market returns: Evidence from OECD countries

Abstract: This paper examines the relationship between political instability and stock market returns using quarterly time series data from 1993 to 2013. In this paper, stock market returns are defined as the returns of the general stock market index and banking index for 18 OECD countries. Five different political instability indicators are constructed in order to measure political uncertainty. The empirical part utilizes the EFA, PCA and GARCH-M methodologies. The findings indicate a direct and an indirect impact betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…The authors concluded that positive news affects stock prices within one week, whilst negative news predicts low stock returns for up to one quarter. Asteriou and Sarantidis (2016) examined the relationship between political instability and stock market returns from 1993 to 2013 using quarterly time series data. They defined stock market returns as the returns of the stock market index and banking index.…”
Section: Miletić (2011) Investigated the Connection Between Dividend mentioning
confidence: 99%
“…The authors concluded that positive news affects stock prices within one week, whilst negative news predicts low stock returns for up to one quarter. Asteriou and Sarantidis (2016) examined the relationship between political instability and stock market returns from 1993 to 2013 using quarterly time series data. They defined stock market returns as the returns of the stock market index and banking index.…”
Section: Miletić (2011) Investigated the Connection Between Dividend mentioning
confidence: 99%
“…Addoum and Kumar (2016) find that the political climate changes affect the returns of firms and industries that are politically sensitive. Using GARCH-M models, Asteriou and Sarantidis (2016) find a negative impact of the political events on the variance of general stock market returns. Further, political unrest, such as a revolution, coup attempts, government/regime changes, protests/demonstrations, strikes and unexpected elections, can have a great influence on a country's home currency.…”
Section: Literature Reviewmentioning
confidence: 96%
“…terms of trade (Chowdhury 2012), capital flows (Jongwanich and Kohpaiboon 2013;Bouraoui 2015), oil prices (Beckmann, Czudaj, and Pilbeam 2015;Basher, Haug, and Sadorsky 2016). Asteriou and Sarantidis (2016) noted that political uncertainty has a negative effect on stock returns. Bonfiglioli and Gancia (2018) show that economic uncertainty has positive and significant effects on the adoption of reforms.…”
Section: Political Stabilitymentioning
confidence: 99%